Sarcoidosis associated pulmonary hypertension - Pauliana; Suryana, Ketut; Schoeck, Heinz P. G. (International Journal of Research in Medical Sciences, 2024)
Sarcoidosis is a multisystem inflammatory disease of unknown etiology that can be manifested as non-caseating granulomas, predominantly in the lungs and intrathoracic lymph nodes. Pulmonary hypertension is known as one of the complications of sarcoidosis and is associated with increased mortality. The incidence of sarcoidosis associated pulmonary hypertension (SAPH) varies between 5 to 20% and the prevalence is unknown. SAPH is classified as group V because of its multifactorial mechanism, it can be caused by pulmonary arterial hypertension, sarcoid cardiomyopathy, hypoxia, chronic thromboembolic pulmonary hypertension disease, and other mechanism like thoracic lymphadenopathy and fibrosing mediastinal, and increasing pulmonary vasoreactivity. SAPH patients have worsening dyspnea or sometimes signs of right-sided heart failure. Patients with SAPH reduced in pulmonary function test (6-minute walk distance (6MWD), diffusing capacity for carbon monoxide (DLCO), another test can be done are chest X-ray, high-resolution chest computed tomography (CT) scan, echocardiography, and right heart catheterization (RHC) as gold standard. The optimal management strategy for pulmonary hypertension associated with sarcoidosis is still unknown. The treatment involved in use of supplemental oxygen, systemic anti-inflammatory medication, pulmonary vasodilators, prostacyclin, endothelin receptor antagonists, phosphodiesterase 5 inhibitors even lung transplantation. SAPH is associated with significant morbidity and mortality. Patients with SAPH have 7-fold increase in risk for all-cause mortality when compare to sarcoidosis patients without PH, even when adjusted for age and pulmonary function.